2015
DOI: 10.1096/fj.14-268508
|View full text |Cite
|
Sign up to set email alerts
|

ACTH controls thymocyte homeostasis independent of glucocorticoids

Abstract: It has been known for decades that lowering the circulating glucocorticoid (GC) concentration as in Addison's disease or after removing the adrenals results in thymus enlargement, largely due to thymocyte expansion. This has been attributed to the loss of the proapoptotic effects on thymocytes by adrenal GCs. Here, we test this concept and report that ACTH directly controls thymic growth post-adrenalectomy (ADX) independent of the proapoptotic effect of GCs. This was supported by the finding that ADX caused th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Adrenalectomized mice treated with ACTH under conditions repressing endogenous ACTH secretion exhibit an increase in the number of thymocytes and splenic naive T-cells compared with control animals. These results show that ACTH directly controls thymocyte homeostasis independently of circulating GC (Talaber et al 2015).…”
Section: Acth and Thymus Growthmentioning
confidence: 55%
“…Adrenalectomized mice treated with ACTH under conditions repressing endogenous ACTH secretion exhibit an increase in the number of thymocytes and splenic naive T-cells compared with control animals. These results show that ACTH directly controls thymocyte homeostasis independently of circulating GC (Talaber et al 2015).…”
Section: Acth and Thymus Growthmentioning
confidence: 55%
“…118,119 The adrencorticotropic hormone receptor, melanocortin receptor subtype 2, is expressed on TECs and its activation regulates thymo cyte expansion when the systemic concentration of glucocorticoid is low. 120 The intrathymic production of corticotropinreleasing factor by thymocytes has also been reported. 121 Taken together, these findings suggest that a circuitry, similar to that seen in the hypothalamus-pituitaryadrenal axis, might also occur within the thymus, but this system needs to be investigated further.…”
Section: Sex Hormonesmentioning
confidence: 96%
“…There is also evidence for ACTH receptors on lymphocytes (70), although the functional significance of this remains difficult to ascertain. More recently, it has been shown that ACTH controls growth of the thymus and that this is not via stimulation by glucocorticoids (392).…”
Section: Role Of Acth In Lymphocytesmentioning
confidence: 99%